Seismic fragility analysis based on artificial ground motions and surrogate modeling of validated structural simulators. (23rd March 2021) - Abbiati, Giuseppe; Broccardo, Marco; Abdallah, Imad; Marelli, Stefano; Paolacci, Fabrizio
Abstract: This study introduces a computational framework for efficient and accurate seismic fragility analysis based on a combination of artificial ground motion modeling, polynomial‐chaos‐based global sensitivity analysis, and hierarchical kriging surrogate modeling. The framework follows the philosophy of the Performance‐Based Earthquake Engineering PEER approach, where the fragility analysis is decoupled from hazard analysis. This study addresses three criticalities that are present in the current practice. Namely, reduced size of hazard‐consistent size‐specific ensembles of seismic records, validation of structural simulators against large‐scale experiments, high computational cost for accurate fragility estimates. The effectiveness of the proposed framework is demonstrated for the Rio Torto Bridge, recently tested using hybrid simulation within the RETRO project.